Canada’s Long-Term Strategic Limitations: Technology and Strategic Choice in Defence Debates, 1887-1959 - Keess, John (Scientia Canadensis)

(untitled) (CSTHA/AHSTC, 2023)
In surveys of Canadian military history, decisions on force design — which involves choosing between investments in different military technologies — are usually framed in the political criteria of sacrificing or preserving Canadian sovereignty. This article argues that Canadian strategic choice is not shaped by either politics or technology, but by the relationship between military technology and Canadian geography. The relationship between these factors provides a strategic context which then shapes the choices open to policy-makers. These contexts reflect two modes: those where there is a direct military threat to Canadian security and those where there is a relative one. The article employs three case studies, debates on Canadian naval policy (1887-1918), changing approaches to defence cooperation with the United States between 1918 and 1945, and debates on Canadian air defence in the early Cold War (1945-1959), to examine how decision-makers understood and acted on absolute threats and the technologies which underwrote them.